New Flame Retardant and Antimicrobial Paints Based on Epoxy Paint Incorporated by Hexachlorocylodiphosphazane Derivatives for Protective Coating - El-Wahab, H. Abd; Mohamed, Salah A.A.; Gomaa, Islam (Journal of Coating Science and Technology, 2019)
Flame retardants can be incorporated into polymeric material either as additives or as reactive materials. Additive type flame retardants are widely used by means of blending them with a specific polymeric material. In this particular research, hexachlorocylodiphosphazane derivatives type (I-II) were synthesized for use as flame retardant and antimicrobial additives with epoxy varnish. These additives are physically incorporated into the epoxy varnish formula. Experimental coatings were manufactured on a laboratory scale and applied by brush on wood and steel panels. The fire retardant ability of each coating type was characterized using the limiting oxygen index (LOI) test. The mechanical properties of these flame retardants were also examined to evaluate the drawbacks of the additives. Results of the LOI indicated that coating with these compounds containing chlorine, nitrogen and phosphorus exhibit a very good retardant effect, when blended with epoxy varnish comparing with the blanket sample which not contain on the hexachlorocylodiphosphazane derivative as a additives. The hexachlorocylodiphosphazane derivative also exhibit mild results as preservative against microbiological attack. The mechanical properties of the painted dry films were investigated acordinting to ASTM.